Search for a Monetary Propagation Mechanism - Shi Shouyong (Queen's University, Department of Economics, 1997)
This paper examines a monetary propagation mechanism in an economy where exchnages in goods and labor markets involve costly search. It is shown that an increase in the money growth rate increases steady state employment and output when the money growth rate is low but reduces steady state and output when the money growth rate is already high. The model produces persistent, hump-shaped responses in employment and output to money growth shocks even when the shocks have no persistence. The model also generates desirable features on job vacancy, sales, inventory, and the velocity of money. All these features emerge here in an economy with perfectly flexible prices and wages.
Keywords: E30; E40; 330; Search; Monetary propagation; Inventory; Hump shape